1992
DOI: 10.1063/1.107012
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced current density J c and extended irreversibility in single-crystal Bi2Sr2Ca1Cu2O8 via linear defects from heavy ion irradiation

Abstract: Large enhancements in the critical current density Jc were produced in single crystals of the high-temperature superconductor Bi2Sr2Ca1Cu2O8 by irradiation with high energy Sn ions. In addition, the irreversibility line was moved to considerably higher magnetic fields. In contrast with analogous studies on Y1Ba2Cu3O7, there was little, if any, selective pinning when the magnetizing field was applied parallel to the linear, ion-damage-produced tracks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(40 citation statements)
references
References 14 publications
4
35
1
Order By: Relevance
“…Kirk (3) , Y.R. Sun (4) , F. Holtzberg (,) , and C. Feild (1) (,) IBM Research, Yorktown Heights NY 10598-0218, USA (2) Oak Ridge National Laboratory, Oak Ridge TN 37831-6061, USA * 'Argonne National Laboratory, Argonne IL 60439, USA * 'Department of Physics, University of Tennessee, Knoxville, TN 37996, USA RECENTLY we have shown that aligned columns of damaged material in high temperature superconductors, installed by the irradiation with swift (~GeV) heavy ions such as Sn, pin magnetic vortices much more effectively than point defects .…”
Section: Disclaimermentioning
confidence: 99%
See 1 more Smart Citation
“…Kirk (3) , Y.R. Sun (4) , F. Holtzberg (,) , and C. Feild (1) (,) IBM Research, Yorktown Heights NY 10598-0218, USA (2) Oak Ridge National Laboratory, Oak Ridge TN 37831-6061, USA * 'Argonne National Laboratory, Argonne IL 60439, USA * 'Department of Physics, University of Tennessee, Knoxville, TN 37996, USA RECENTLY we have shown that aligned columns of damaged material in high temperature superconductors, installed by the irradiation with swift (~GeV) heavy ions such as Sn, pin magnetic vortices much more effectively than point defects .…”
Section: Disclaimermentioning
confidence: 99%
“…Images are produced from the best available original document (l) ' (a) , L. Krusin-Elbaum (,) , J.R. Thompson (2) (4) , R. Wheeler (3) , A.D.…”
Section: Disclaimermentioning
confidence: 99%
“…The introduction of columnar defects by high energy heavy ion irradiation has been shown to be capable of producing large enhancements in the magnetization .Ic and in raising the irreversibility line in single crystal Bi-2212 [4]. Both of these factors increase the useful operating field at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques for creating defects have been investigated in the past, including chemical doping, 1-4 shock compaction, 5,6 and particle irradiation. [7][8][9][10][11][12][13][14] Although these techniques have proven to be very effective for increasing J c , the need for larger J c values still exists.…”
mentioning
confidence: 98%